Unexpected diversity of Isidoides (Anthozoa: Octocorallia: Isidoidae) revealed by morphology and phylogenomic analysis with descriptions of three new species - Yu Xu; Jaret P. Bilewitch; Eric Pante; Zifeng Zhan; Sadie Mills; Malcolm R. Clark; Kuidong Xu (Molecular Phylogenetics and Evolution, 2026)

Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Dynamics of nutrients in the Beibu Gulf: distributions, diapycnal transport, and budget during the autumn season - Hao Eric Wang; Jinwen Liu; Wenbin Zou; Lifang Wang; Jinyang Yu; Lunbi Wu; Ying He; Shuh-ji Kao; Chuanjun Du; Qiang Lian (Marine Environmental Research, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

The hidden infectious disease-related sepsis risk of wildfire-specific PM2.5 - Rahini Mahendran; Rongbin Xu; Lei Zhang; Tingting Ye; Yiwen Zhang; Zhihu Xu; Wenzhong Huang; Zhengyu Yang; Michael J. Abramson; Fay H. Johnston; Luke Knibbs; Simon Hales; et al. (Environmental Research, 2026)

Corrigendum to “Ventilation–energy trade-offs in retrofitted Hong Kong wet markets” [Energy Build. 355 (2026) 116918] - Hongshan Guo; Yu Chang; Yichun Li; Ying Zhou; Qingyao Qiao; Chun Yin Lai; Eric Schuldenfrei (Energy and Buildings, 2026)

Sedimentary DNA and Fossil Archives Reveal Long‐Term Phytoplankton Shifts and Their Biogeochemical Influence in a Subtropical Lake - Yu Zhao; Jianan Zheng; Meifang Zhong; Wenxiu Zheng; Bo Qin; Kexin Zhu; Chenxue Zhang; Yanjie Zhao; Enlou Zhang; Eric Capo; Rong Wang (Molecular Ecology, 2026)
Understanding long‐term phytoplankton community dynamics is essential for assessing ecological resilience and informing lake management under global change. However, centennial‐scale patterns of phytoplankton dynamics remain poorly resolved due to the limited taxonomic resolution of traditional fossil‐based paleoecological approaches. In this study, a combination of sedimentary DNA (sedDNA) and subfossil diatom analysis was used to investigate changes in the phytoplankton community over the past two centuries and associated sedimentary biogeochemical responses in Lake Xiliang, a subtropical lake in the Yangtze River Basin, China. The sedDNA data captured major shifts in both eukaryotic and cyanobacterial communities, revealing distinct ecological phases linked to human activities and regional climate warming. Under near‐natural conditions with minimal human disturbance, phytoplankton communities typically exhibit low diversity and are characterized by oligotrophic taxa such as xanthophytes and Gyrosigma . After the 1930s, increases in epiphytic Staurosira and declines in tychoplanktonic Aulacoseira suggest reduced river–lake connectivity and weaker water‐column turbulence following the construction of the Jinshui Sluice, likely facilitating macrophyte expansion. In recent decades, intensified anthropogenic pressures combined with regional warming have driven a shift toward more diverse phytoplankton assemblages enriched in cyanobacteria, reflecting elevated nutrient inputs and rising temperatures. The observed associations between phytoplankton community changes and sedimentary geochemical proxies suggest that phytoplankton dynamics may not only have responded to environmental change but also contributed to sedimentary biogeochemical cycling, particularly total organic carbon accumulation and calcium‐related processes such as photosynthesis‐induced carbonate precipitation. These findings illustrate long‐term phytoplankton community dynamics and underscore the value of sedDNA for reconstructing ecological trajectories in lake ecosystems.

From coast to coast: Understanding electric vehicle adoption across Canadian regions - Mwendwa Kiko; Jiaxin Zhang; Yu Zhang; Eric J. Miller (Transportation Research Part D: Transport and Environment, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Source-specific short-term-ozone exposure and specific cancer mortality risk: A multi-country study in 11,215 communities - Pei Yu; Rongbin Xu; Wenzhong Huang; Yanming Liu; Zhengyu Yang; Michael J. Abramson; Eric Lavigne; Simon Hales; Lidia Morawska; Paulo H.N. Saldiva; Fay H. Johnston; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Corrigendum to “Multispectral airborne laser scanning for tree species classification: A benchmark of machine learning and deep learning algorithms” [ISPRS J. Photogramm. Remote Sens. 233 (2026) 278–309] - Josef Taher; Eric Hyyppä; Matti Hyyppä; Klaara Salolahti; Xiaowei Yu; Leena Matikainen; Antero Kukko; Matti Lehtomäki; Harri Kaartinen; Sopitta Thurachen; Paula Litkey; Ville Luoma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Future temperature-related labour loss due to premature deaths: a multi-country study - Bo Wen; Zanfina Ademi; Yao Wu; Rongbin Xu; Pei Yu; Yanming Liu; Wenhua Yu; Tingting Ye; Wenzhong Huang; Zhengyu Yang; Yiwen Zhang; Yuxi Zhang; et al. (Environmental Research, 2026)

Nutrient regimes shaping the diatom-dinoflagellate interdecadal succession in coastal temperate waters of China - Kan Chen; Keqiang Li; Guangshen Tan; Peiyi Gao; Guangmin Zhen; Rui Yang; Kunlong Yu; Xiansheng Zhang; Xiaoru Cui; Dongliang Lu; Shanqiao Chen; Eric P. Achterberg; et al. (Water Research, 2026)

Multispectral airborne laser scanning for tree species classification: A benchmark of machine learning and deep learning algorithms - Josef Taher; Eric Hyyppä; Matti Hyyppä; Klaara Salolahti; Xiaowei Yu; Leena Matikainen; Antero Kukko; Matti Lehtomäki; Harri Kaartinen; Sopitta Thurachen; Paula Litkey; Ville Luoma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Ventilation–energy trade-offs in retrofitted Hong Kong wet markets - Hongshan Guo; Yu Chang; Yichun Li; Ying Zhou; Qingyao Qiao; Chun Yin Lai; Eric Schuldenfrei (Energy and Buildings, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

Waste minimization in zeolites synthesis from coal fly ash by recycling alkaline waste - Wei Feng; Brent Young; Wei Yu; Xuehai Yu; Eric F. May; Dong Xu; Gang Kevin Li (Journal of Environmental Chemical Engineering, 2026)

Deep-learning-based energy consumption prediction of coal mine air heating units (CMAHU): case studies of China’s Northwest coal mines under extreme low temperature conditions - Peijun FENG; Yu ZHENG; Siu-Yeung CHO; Ka Wai Eric CHENG; Xiaoyue YI; Siqi BU (Energy and Buildings, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Research progress of contact-electro-catalysis in the remediation of emerging pollutants: exploration from mechanism to application - Yu Jiang; Han Yu; Xinping Chen; Linzi Wu; Zhanqiang Fang; Pokeung Eric Tsang (Environmental Research, 2025)

Genome-Wide Association Study of Glucocerebrosidase Activity Modifiers - Emma N. Somerville; Lynne Krohn; Konstantin Senkevich; Eric Yu; Jamil Ahmad; Farnaz Asayesh; Jennifer A. Ruskey; Dan Spiegelman; Stanley Fahn; Cheryl Waters; S. Pablo Sardi; Roy N. Alcalay; et al. (Molecular Neurobiology, 2025)
One of the most common genetic risk factors for Parkinson’s disease (PD) is variants in GBA1 , which encodes the lysosomal enzyme glucocerebrosidase (GCase). GCase deficiency has been associated with an increased PD risk, but not all individuals with low GCase activity are carriers of GBA1 mutations, suggesting other factors may be acting as modifiers. We aimed to discover common variants associated with GCase activity, as well as replicate previously reported associations, by performing a genome-wide association study using two independent cohorts: a Columbia University cohort consisting of 697 PD cases and 347 controls and the Parkinson’s Progression Markers Initiative (PPMI) cohort consisting of 357 PD cases and 163 controls. As expected, GBA1 variants have the strongest association with decreased activity, led by N370S (beta = − 4.36, se = 0.32, p = 5.05e − 43). We also identify a novel association in the GAA locus (encoding for acid alpha-glucosidase, beta = − 0.96, se = 0.17, p = 5.23e − 09) that may be the result of an interaction between GCase and acid alpha-glucosidase based on various interaction analyses. Lastly, we show that several PD-risk loci are potentially associated with GCase activity. Further research will be needed to replicate and validate our findings and to uncover the functional connection between acid alpha-glucosidase and GCase.

Has research on health co-benefits influenced urban climate and transport planning in the United Kingdom, United States, Japan, and France? - Zahrah Ali; Eric Zusman; Bing-yu Chiu; Matthew Hengesbaugh (Sustainability Science, 2025)

Understanding the mechanisms in lithium-ion selectivity enhancement by coating cation exchange membranes with doped polypyrrole - Lingchen Kong; Li Chen; Eric Palacios; Yongchang Yu; Nicole Conte; Meng Shen; Xitong Liu (Desalination, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Regulating multi-directional passenger flow: Impact of obstacle position and flow level on pedestrian merging process - Hanchen Yu; Nan Jiang; Maoyu Li; Xinmiao Jia; Jixin Shi; Eric Wai Ming Lee; Lizhong Yang (Tunnelling and Underground Space Technology, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Biomonitoring of toxic metal exposure in New Jersey adults in 2015–2018 - Chang Ho Yu; Eric Bind; Andrew Steffens; Douglas Haltmeier; Collin D. Riker; Jhindan Mukherjee; Zhihua Tina Fan (International Journal of Hygiene and Environmental Health, 2025)

Methane production related to microbiota in dairy cattle feces - Jian Liu; Meng Zhou; Lifeng Zhou; Run Dang; Leilei Xiao; Yang Tan; Meng Li; Jiafeng Yu; Peng Zhang; Marcela Hernández; Eric Lichtfouse (Environmental Research, 2025)

Contamination of Per- And Polyfluoroalkyl Substances in Freshwater Fish from Areas Adjacent to Three Former and Active Military Facilities in New York - Yu Chen; Kaitlin M. Gattoni; Eric Paul; Patrick J. Sullivan; Abigail C. Valachovic; Leili Vogl (Archives of Environmental Contamination and Toxicology, 2025)

Imagine, Discover, Inspire: Proceedings of the 4th International Conference of the Trisomy 21 Research Society - Lisi Flores-Aguilar; Eric D. Hamlett; Paula Araya; Eugenio Barone; Anita Bhattacharyya; Maria Carmona-Iragui; Li Chan; Brad Christian; Alberto C. S. Costa; Floriana Costanzo; Laura Del Hoyo Soriano; Mara Dierssen; et al. (NeuroMolecular Medicine, 2025)
Down syndrome (DS) or trisomy 21 (T21) is present in a significant number of children and adults around the world and is associated with cognitive and medical challenges. Through research, the T21 Research Society (T21RS), established in 2014, unites a worldwide community dedicated to understanding the impact of T21 on biological systems and improving the quality of life of people with DS across the lifespan. T21RS hosts an international conference every two years to support collaboration, dissemination, and information sharing for this goal. In 2022, T21RS hosted an international conference in Long Beach, California, from June 9 to 12. The conference, attended by 483 people including scientists, families, self-advocates, and industry representatives from 17 countries, was a dynamic and interactive meeting that shared discoveries from international research teams. This summary highlights the scientific discoveries shared at the 4th T21RS meeting with the Imagine, Discover, Inspire theme.

Sphingomyelin-enriched milk phospholipids offer superior benefits in improving the physicochemical properties, microstructure, and surface characteristics of infant formula - Yue Pan; Xueying Zhang; Qingquan Yan; Jiayu Li; Kouadio Jean Eric-Parfait Kouame; Xiaodong Li; Lu Liu; Xuexing Zong; Kuolin Si; Xiaoyan Liu; Mengna Yu (Food Chemistry, 2025)

Intercropping: ecosystem functioning and sustainable agriculture - Rui-Peng Yu; Dorte B. Dresbøll; Maria R. Finckh; Eric Justes; Wopke van der Werf; Andrew Fletcher; Georg Carlsson; Long Li (Plant and Soil, 2025)

New insights into the merging behavior of pedestrians: Quantification of lane competition level - Hanchen Yu; Nan Jiang; Maoyu Li; Xinmiao Jia; Yifan Zhuang; Lizhong Yang; Eric Wai Ming Lee (Tunnelling and Underground Space Technology, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Storm surge induced by Tropical Storm Pabuk (2019) and its impact by track variation scenarios on the Thailand coast - Yu-Lin Tsai; Tso-Ren Wu; Eric Yen; Veerachai Tanpipat; Chuao-Yao Lin (Natural Hazards, 2024)

Discovery of a novel marine bacterial AIEgen that lights up specific G-quadruplexes - Wenkang Ye; Xinnan Wang; Parvej Alam; Changdong Liu; Monica C. Suen; Jianwei Tang; Herman H.Y. Sung; Ian D. Williams; Eric Y. Yu; Jacky W.Y. Lam; Guang Zhu; Ben-Zhong Tang; et al. (Chemical Engineering Journal, 2024)

ICH M10 Bioanalytical Method Validation Guideline-1 year Later - Faye Vazvaei-Smith; Enaksha Wickremsinhe; Eric Woolf; Chongwoo Yu (The AAPS Journal, 2024)
The International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) adopted Guideline M10 entitled "Bioanalytical Method Validation and Study Sample Analysis" in May 2022. In October 2023, approximately one year after the adoption of the ICH M10 guideline, a "Hot Topic" session was held during the AAPS PharmSci 360 meeting to discuss the implementation of the guideline. The session focused on items the bioanalytical community felt were challenging to implement or ambiguous within the guideline. These topics included cross-validation, parallelism, comparative bioavailability studies, combination drug stability, endogenous analyte bioanalysis, and dilution QCs. In addition, the regulatory perspective on the guideline was presented. This report provides a summary of the Hot Topic session. Graphical Abstract

Quantifying the Role of the Eddy Transfer Coefficient in Simulating the Response of the Southern Ocean Meridional Overturning Circulation to Enhanced Westerlies in a Coarse-resolution Model - Yiwen Li; Hailong Liu; Pengfei Lin; Eric P. Chassignet; Zipeng Yu; Fanghua Wu (Advances in Atmospheric Sciences, 2024)

Controls on distributions of aluminium, manganese and cobalt in the South Atlantic Ocean along GEOTRACES transect GA10 - Xue-Gang Chen; Angela Milne; Jessica K. Klar; Martha Gledhill; Maeve C. Lohan; Yu-Te Hsieh; Gideon M. Henderson; E. Malcolm S. Woodward; Eric P. Achterberg (Geochimica et Cosmochimica Acta, 2024)

Improving lipid digestion by modulating interfacial structure of fat globule based on milk fat globule membrane and different phospholipids - Qian Ma; Meng Sun; Yanjie Zhao; Shuo Chen; Xiaodong Li; Lu Liu; Xiuxiu Zhang; Yuxin Wang; Kouadio Jean Eric-Parfait Kouame; Xiaoxue Yu (Food Hydrocolloids, 2024)

Ion transfer mediated by TEMPO in ionophore-doped thin films for multi-ion sensing by cyclic voltammetry - Gabriel J. Mattos; Justine A. Rothen; Nikolai Yu Tiuftiakov; Eric Bakker (Analytica Chimica Acta, 2024)

Continuity between NASA MODIS Collection 6.1 and VIIRS Collection 2 land products - Miguel O. Román; Chris Justice; Ian Paynter; Peter B. Boucher; Sadashiva Devadiga; Arthur Endsley; Angela Erb; Mark Friedl; Huilin Gao; Louis Giglio; Josh M. Gray; Dorothy Hall; et al. (Remote Sensing of Environment, 2024)

Roles of changes in land weathering intensity in the Nd cycle of the South China Sea during the past 30 kyr as inferred from neodymium isotopic composition in foraminifera - Yi Huang; Christophe Colin; Zhifei Liu; Bertaz Joffrey; Arnaud Dapoigny; Eric Douville; Zhaojie Yu; Andrew Tien-Shun Lin (Chemical Geology, 2024)

Large contributions of emission reductions and meteorological conditions to the abatement of PM2.5 in Beijing during the 24th Winter Olympic Games in 2022 - Yaping Jiang; Shaocai Yu; Xue Chen; Yibo Zhang; Mengying Li; Zhen Li; Zhe Song; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Journal of Environmental Sciences, 2024)

New insights into bee pollen: Nutrients, phytochemicals, functions and wall-disruption - Jiangtao Qiao; Yu Zhang; Eric Haubruge; Kai Wang; Hesham R. El-Seedi; Jie Dong; Xiang Xu; Hongcheng Zhang (Food Research International, 2024)

Unrecognized pollution by inorganic condensable particulate matter in the atmosphere - Mengying Li; Shaocai Yu; Pengfei Li; Xue Chen; Zhe Song; Weiping Liu; Xiaoye Zhang; Meigen Zhang; Yele Sun; Zirui Liu; Jingkun Jiang; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2024)

Focal mechanism of a Late Triassic large magnitude earthquake along the Longmen Shan fault belt, eastern Tibetan Plateau - Lei Zhang; Haibing Li; Eric C. Ferré; Zhiming Sun; Yu-Min Chou; Yong Cao; Huan Wang; Yong Zheng; Chenglong Li; Elham Hosseinzadehsabeti (Journal of Structural Geology, 2024)

Introduction of isotopically light barium from the Rainbow hydrothermal system into the deep Atlantic Ocean - Zhouling Zhang; Linbin Zhou; Xue-Gang Chen; Eric P. Achterberg; Yang Yu; Ed Hathorne; Zvi Steiner; Christopher Siebert; Martin Frank (Earth and Planetary Science Letters, 2024)

A facile synthesis of stable copper-based core-shell catalysts for highly efficient 4-nitrophenol reduction and benzyl alcohol oxidation - Jiakang Liu; Han Yang; Ufuoma I. Kara; Eric Boerner; Yiqian Luo; Haitao Yu; Yang Xu; Xiaoguang Wang; Kun Huang (Chemical Engineering Journal, 2024)

Active subduction and strain partitioning in western Myanmar revealed by a dense survey GNSS network - Eric O. Lindsey; Yu Wang; Lin Thu Aung; Jeng-Hann Chong; Qiang Qiu; Rishav Mallick; Lujia Feng; Pyae Sone Aung; Tha Zin Htet Tin; Saw Myat Min; Kyle Bradley; Oo Than; et al. (Earth and Planetary Science Letters, 2023)

Biomethane is produced by acetate cleavage, not direct interspecies electron transfer: genome-centric view and carbon isotope - Jian Liu; Jiafeng Yu; Yang Tan; Run Dang; Meng Zhou; Marcela Hernández; Eric Lichtfouse; Leilei Xiao (Bioresource Technology, 2023)

Dietary exposure to sulfamethazine alters fish intestinal homeostasis and promotes resistance gene transfer - Xiaohan Yin; Youshen Li; Yawen Liu; Jingyi Zheng; Xiaoxuan Yu; Yongyu Li; Eric P. Achterberg; Xinhong Wang (Aquatic Toxicology, 2023)

Assessment of Scanning Mobility Particle Sizer (SMPS) for online monitoring of delivered dose in an in vitro aerosol exposure system - Sripriya Nannu Shankar; Kiran Mital; Eric Le; Gregory S. Lewis; Arantzazu Eiguren-Fernandez; Tara Sabo-Attwood; Chang-Yu Wu (Toxicology in Vitro, 2023)

Time-lapse imaging of seismic scattering property and velocity in the northeastern Japan - Takashi Hirose; Qing-Yu Wang; Michel Campillo; Hisashi Nakahara; Ludovic Margerin; Eric Larose; Takeshi Nishimura (Earth and Planetary Science Letters, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Understanding grain virtual water flux dynamics and drivers from a socio-ecohydrological perspective: A case study of landlocked developing countries of Africa - Hubert Hirwa; Fadong Li; Simon Measho; Gang Chen; Fabien Muhirwa; Qiuying Zhang; Alphonse Kayiranga; Yunfeng Qiao; Peifang Leng; Chao Tian; Guang Yang; Jean Baptiste Baranyika; et al. (Journal of Cleaner Production, 2023)

Higher efficiency and lower environmental impact of membrane separation for carbon dioxide capture in coal power plants - Yan Wang; Zhen Pan; Wenxiang Zhang; Shaochang Huang; Guojie Yu; Mohamad Reza Soltanian; Eric Lichtfouse; Zhien Zhang (Environmental Chemistry Letters, 2023)

Heritable methylation marks associated with prostate cancer risk - James G. Dowty; Chenglong Yu; Mahnaz Hosseinpour; Jihoon Eric Joo; Ee Ming Wong; Tu Nguyen-Dumont; Joseph Rosenbluh; Graham G. Giles; Roger L. Milne; Robert J. MacInnis; Pierre-Antoine Dugué; Melissa C. Southey (Familial Cancer, 2023)
DNA methylation marks that are inherited from parents to offspring are known to play a role in cancer risk and could explain part of the familial risk for cancer. We therefore conducted a genome-wide search for heritable methylation marks associated with prostate cancer risk. Peripheral blood DNA methylation was measured for 133 of the 469 members of 25 multiple-case prostate cancer families, using the EPIC array. We used these families to systematically search the genome for methylation marks with Mendelian patterns of inheritance, then we tested the 1,000 most heritable marks for association with prostate cancer risk. After correcting for multiple testing, 41 heritable methylation marks were associated with prostate cancer risk. Separate analyses, based on 869 incident cases and 869 controls from a prospective cohort study, showed that 9 of these marks near the metastable epiallele VTRNA2-1 were also nominally associated with aggressive prostate cancer risk in the population.

Pilot-scale demonstration of dissolved organic nitrogen removal from an advanced water reclamation facility using enhanced coagulation - Tayebeh Goli; Yasha Jathan; Yu Yang; Krishna R. Pagilla; Eric A. Marchand (Science of The Total Environment, 2023)

Solvent engineering for triple cationic ITO-based mesoscopic tin perovskite solar cells - Donghoon Song; Hung-Yu Tseng; Sudhakar Narra; I-Hua Tsai; Eric Wei-Guang Diau (Chemical Engineering Journal, 2023)

Interfacial solar steam generation by wood-based devices to produce drinking water: a review - Roya Mehrkhah; Elaheh K. Goharshadi; Eric Lichtfouse; Ho Seon Ahn; Somchai Wongwises; Wei Yu; Omid Mahian (Environmental Chemistry Letters, 2023)

What is the role of disturbance in catalyzing spatial shifts in forest composition and tree species biomass under climate change? - Yu Liang; Eric J. Gustafson; Hong S. He; Josep M. Serra‐Diaz; Matthew J. Duveneck; Jonathan R. Thompson (Global Change Biology, 2023)
Mounting evidence suggests that climate change will cause shifts of tree species range and abundance (biomass). Abundance changes under climate change are likely to occur prior to a detectable range shift. Disturbances are expected to directly affect tree species abundance and composition, and could profoundly influence tree species spatial distribution within a geographical region. However, how multiple disturbance regimes will interact with changing climate to alter the spatial distribution of species abundance remains unclear. We simulated such forest demographic processes using a forest landscape succession and disturbance model (LANDIS‐II) parameterized with forest inventory data in the northeastern United States. Our study incorporated climate change under a high‐emission future and disturbance regimes varying with gradients of intensities and spatial extents. The results suggest that disturbances catalyze changes in tree species abundance and composition under a changing climate, but the effects of disturbances differ by intensity and extent. Moderate disturbances and large extent disturbances have limited effects, while high‐intensity disturbances accelerate changes by removing cohorts of mid‐ and late‐successional species, creating opportunities for early‐successional species. High‐intensity disturbances result in the northern movement of early‐successional species and the southern movement of late‐successional species abundances. Our study is among the first to systematically investigate how disturbance extent and intensity interact to determine the spatial distribution of changes in species abundance and forest composition.

Marine debris awareness improvement using immersive virtual reality - Sayali Joshi; Yu Wang; Eric Sparks; Mohammad Marufuzzaman; Mandy Sartain; Junfeng Ma (Marine Pollution Bulletin, 2023)

Metabolic clearance of oxaloacetate and mitochondrial complex II respiration: Divergent control in skeletal muscle and brown adipose tissue - Liping Yu; Brian D. Fink; Ritu Som; Adam J. Rauckhorst; Eric B. Taylor; William I. Sivitz (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Effects of Bacillus sp. and Lactobacillus sp. combination as a water additive on the culture pond water and growth performance of hybrid grouper (Epinephelus fuscoguttatus × Epinephelus polyphekadion) - Jianpeng Huang; Eric Amenyogbe; Guanghai Ou; Yu Li; Zhenwei Wen; Xingtao Jiang; Gang Chen (Frontiers in Marine Science, 2022)
The individual Probiotic application has become increasingly widespread in aquaculture and has been extensively studied. However, investigating probiotics as water additives in the grouper culture is still lacking. This study evaluated the functional efficacy of the Bacillus subtilis CICC 10071 (3 × 1011 CFU / g) and Lactobacillus sp. (8 × 1011 CFU / g) combination in a 1:1 ratio on the rearing water quality, water microbial community structure, and growth performance of hybrid grouper. Depending on the additive concentrations of probiotics, we designed four groups, each in triplicate: control (WT, 0g/m3), low concentration (WL, 0.038g/m3), middle concentration (WM, 0.075g/m3), and high concentration (WH, 0.113g/m3). The result shows that throughout the 22-day feeding period, the water supplementation of probiotics significantly decreased Ammonia (NH3) and nitrite (NO2-) in culture water. Final weight (FW), Specific growth rate (SGR), and Weight gain rate (WGR) in treated groups were higher than that in the control group (P<0.05). Analysis of water microbiota revealed that the dominant phylum Bacteroidetes, Proteobacteria, Cyanobacteria, and Actinobacteria enriched in the culture water. Furthermore, we found that the Probiotics combination could significantly reduce the abundance of Cetobacterium (phyla Fusobacteria) related to ammonia and nitrite. The Phylogenetic Investigation of Communities by Reconstruction of Unobserved States 2 (PICRUSt2) also shows that the 'metabolism of other amino acids and ‘Fatty acid biosynthesis’ functions of water microbiota were reinforced by the addition of the probiotic combination. Thus, the probiotic combination exhibited a range of advantages in the grouper culture environment, and further in-depth studies are needed.

The redox state of the plastoquinone (PQ) pool is connected to thylakoid lipid saturation in a marine diatom - Kuan Yu Cheong; Juliette Jouhet; Eric Maréchal; Paul G. Falkowski (Photosynthesis Research, 2022)

Local production, downward and regional transport aggravated surface ozone pollution during the historical orange-alert large-scale ozone episode in eastern China - Yibo Zhang; Shaocai Yu; Xue Chen; Zhen Li; Mengying Li; Zhe Song; Weiping Liu; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Environmental Chemistry Letters, 2022)

Safety and Pharmacokinetics of Intranasally Administered Heparin - Hannah M. Harris; Katherine L. Boyet; Hao Liu; Rohini Dwivedi; Nicole M. Ashpole; Ritesh Tandon; Gene L. Bidwell; Zhi Cheng; Lauren A. Fassero; Christian S. Yu; Vitor H. Pomin; Dipanwita Mitra; et al. (Pharmaceutical Research, 2022)

Non-stop industries were the main source of air pollution during the 2020 coronavirus lockdown in the North China Plain - Zhen Li; Shaocai Yu; Mengying Li; Xue Chen; Yibo Zhang; Jiali Li; Yapping Jiang; Weiping Liu; Pengfei Li; Eric Lichtfouse (Environmental Chemistry Letters, 2022)

Biodiversity alleviates the decrease of grassland multifunctionality under grazing disturbance: A global meta‐analysis - Ruiyang Zhang; Dashuan Tian; Han Y. H. Chen; Eric W. Seabloom; Guodong Han; Shaopeng Wang; Guirui Yu; Zhaolei Li; Shuli Niu (Global Ecology and Biogeography, 2022)
Aim Biodiversity drives the delivery of multiple ecosystem functions related to carbon and nutrient cycling (ecosystem multifunctionality, EMF), and biodiversity and ecosystem functioning are strongly threatened by intensive grazing in grasslands. However, it remains unclear how biodiversity regulates EMF changes in response to intensive grazing. Location Global. Time period From 1992 to 2018. Major taxa studied Grassland. Methods Here, we conducted a global synthesis using 373 paired observations from 90 published studies to address the responses of plant diversity, EMF and their relationships to grazing disturbance depending on grazing intensity, livestock type, grazing duration, and climatic aridity. Results Our results showed that EMF significantly decreased with increasing grazing intensity, but the negative EMF response was alleviated at high levels of plant diversity. The grazing‐induced changes in EMF increased linearly with the changes in plant diversity, with the slopes increasing by 78.9% from light to heavy grazing. In addition, the grazing‐induced decrease of EMF was stronger with longer grazing duration and more arid climates. Structural equation models suggested that grazing intensity reduced EMF largely via decreasing plant diversity, whereas upsizing livestock type promoted EMF by increasing plant diversity. Main conclusions This study highlights the key role of biodiversity in mediating EMF in response to intensifying grazing disturbance. We call for conservation of biodiversity to maintain grassland multifunctionality and services.

Large scale control of surface ozone by relative humidity observed during warm seasons in China - Mengying Li; Shaocai Yu; Xue Chen; Zhen Li; Yibo Zhang; Liqiang Wang; Weiping Liu; Pengfei Li; Eric Lichtfouse; Daniel Rosenfeld; John H. Seinfeld (Environmental Chemistry Letters, 2021)

miR-181a Mediates Inflammatory Gene Expression After Intracerebral Hemorrhage: An Integrated Analysis of miRNA-seq and mRNA-seq in a Swine ICH Model - Kyle B. Walsh; Kip D. Zimmerman; Xiang Zhang; Stacie L. Demel; Yu Luo; Carl D. Langefeld; Eric Wohleb; Grant Schulert; Daniel Woo; Opeolu Adeoye (Journal of Molecular Neuroscience, 2021)

High resolution mapping of nighttime light and air pollutants during the COVID-19 lockdown in Wuhan - Sheng Zheng; Yuyuan Fu; Yu Sun; Chengjie Zhang; Yueshe Wang; Eric Lichtfouse (Environmental Chemistry Letters, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

Late Cenozoic paleostress reconstruction and stress regimes in Taiyuan basin of the Shanxi rift, North China - Konan Roger Assie; Yu Wang; Huimin Ma; Kouamelan Serge Kouamelan; Eric Thompson Brantson; Koffi Alexis N’ dri; Ohouo Rebecca Mondah (International Journal of Earth Sciences, 2021)

Stranger Things: Organismal Traits of Two Octocorals Associated With Singular Symbiodiniaceae in a High-Latitude Coral Community From Northern Taiwan - Tsai-Hsuan Tony Hsu; Lilian Carlu; Yunli Eric Hsieh; Tzu-Yu Angel Lai; Ching-Wei Wang; Ching-Yun Huang; Shan-Hua Yang; Pei-Ling Wang; Nicolas Sturaro; Vianney Denis (Frontiers in Marine Science, 2020)
Scrutinizing the traits of octocorals that could affect their physiological performance becomes increasingly important as several of these species are observed to become dominant on reefs pressured by the Anthropocene. In the present study, we compare the organismal traits of two branching octocorals Litophyton sp. and Stereonephthya sp. commonly populating in sympatry the high-latitude coral communities of northern Taiwan. Using 13 traits, we describe and compare performance traits in these two symbiotic species that we discuss in light of the association they maintain with their algal partners. Litophyton sp. and Stereonephthya sp. hosted Durusdinium and Gerakladium , respectively. Both genera represent singular associations, with the latter further establishing the first solid report of Gerakladium in octocorals. Traits distinguished two groups explained by the two partnerships considered. Litophyton sp. associated with Durusdinium had significantly higher organic matter, chlorophyll (chl) a , total lipid and lower chl c /chl a ratio than Stereonephthya sp. associated with Gerakladium. The δ 15 N in the host and algae, as well as δ 13 C in the host were also higher in Litophyton species. Although no significant difference was observed in the δ 13 C of the algae, Litophyton sp. presented a significantly higher variance for this trait and for chl a content than Stereonephthya species. Altogether, the traits examined suggested contrasting performances among the two octocorals. Both octocoral species clearly deviate from an autotrophic diet. Litophyton sp. appears to complement its heterotrophic diet with photosynthetically acquired energy, while Stereonephthya sp. tends to be more specialized and benefits relatively little from its symbiotic relationship. Our study calls for greater consideration of the individual variation in octocoral physiology and in the definition of their ecological strategies.

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Unexpected rise of ozone in urban and rural areas, and sulfur dioxide in rural areas during the coronavirus city lockdown in Hangzhou, China: implications for air quality - Liqiang Wang; Mengying Li; Shaocai Yu; Xue Chen; Zhen Li; Yibo Zhang; Linhui Jiang; Yan Xia; Jiali Li; Weiping Liu; Pengfei Li; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2020)

Common source areas of air pollution vary with haze intensity in the Yangtze River Delta, China - Xue Chen; Shaocai Yu; Liqiang Wang; Zhen Li; Yibo Zhang; Mengying Li; Khalid Mehmood; Weiping Liu; Pengfei Li; Eric Lichtfouse; Daniel Rosenfeld; John H. Seinfeld (Environmental Chemistry Letters, 2020)

Mechanisms behind soil N dynamics following cover restoration in degraded land in subtropical China - Xiangzhou Zheng; Cheng Lin; Baoling Guo; Juhua Yu; Hong Ding; Shaoyun Peng; Jinbo Zhang; Eric Ireland; Deli Chen; Christoph Müller; Yushu Zhang (Journal of Soils and Sediments, 2020)

A recombinant infectious bronchitis virus from a chicken with a spike gene closely related to that of a turkey coronavirus - Yan Wang; Xuejiao Cui; Xu Chen; Shixing Yang; Yu Ling; Qianben Song; Su Zhu; Luying Sun; Chuang Li; Yu Li; Xutao Deng; Eric Delwart; et al. (Archives of Virology, 2020)

Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Fraser Davidson; Aida Alvera-Azcárate; Alexander Barth; Gary B. Brassington; Eric P. Chassignet; Emanuela Clementi; Pierre De Mey-Frémaux; Prasanth Divakaran; Christopher Harris; Fabrice Hernandez; Patrick Hogan; Lars R. Hole; et al. (Frontiers in Marine Science, 2019)

High-altitude and long-range transport of aerosols causing regional severe haze during extreme dust storms explains why afforestation does not prevent storms - Ping Guo; Shaocai Yu; Liqiang Wang; Pengfei Li; Zhen Li; Khalid Mehmood; Xue Chen; Weiping Liu; Yannian Zhu; Xing Yu; Kiran Alapaty; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2019)

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Change point analysis of global temperature records - Michelle Yu; Eric Ruggieri (International Journal of Climatology, 2019)
Climate change is the result of complex interactions between a wide array of climatic variables. Over a long period of time, climatic patterns can shift, possibly multiple times. Abrupt shifts that occur over a relatively short period of time are known as change points. During these intervals, different climatic variables may undergo dramatic shifts posing serious consequences for many biological and physical systems. In this paper, we discuss a Bayesian algorithm for detecting the location of change points in time series data. In particular, we utilize our method to analyse five different global surface temperature anomaly data sets, as well as temperature records associated with land, ocean, and different zonal bands in an attempt to identify common features of these data sets. Change points in the five global records were detected between 1902–1917, 1936–1945, and 1963–1976, but do these change points also manifest themselves across other parts of the globe? Our analysis indicates that the timing of change points is consistent from one record to the next, but not all change points appear in all records. In particular, there were more change points in the ocean than on land, and also more change points in southern latitudes than in northern latitudes.

Diltiazem Promotes Regenerative Axon Growth - Eric A. Huebner; Stéphane Budel; Zhaoxin Jiang; Takao Omura; Tammy Szu-Yu Ho; Lee Barrett; Janie S. Merkel; Luis M. Pereira; Nick A. Andrews; Xingxing Wang; Bhagat Singh; Kush Kapur; et al. (Molecular Neurobiology, 2019)

A novel phage from periodontal pockets associated with chronic periodontitis - Yu Zhang; Tong-Ling Shan; Fei Li; Tian Yu; Xi Chen; Xu-Tao Deng; Eric Delwart; Xi-Ping Feng (Virus Genes, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Viral metagenomics reveals significant viruses in the genital tract of apparently healthy dairy cows - Yu Ling; Xiaodan Zhang; Guilan Qi; Shixing Yang; Li Jingjiao; Quan Shen; Xiaochun Wang; Li Cui; Xiuguo Hua; Xutao Deng; Eric Delwart; Wen Zhang (Archives of Virology, 2019)

Asian black bear (Ursus thibetanus) picornavirus related to seal aquamavirus A - Haoning Wang; Wen Zhang; Shixiing Yang; Ning Kong; Hai Yu; Hao Zheng; Fei Gao; Wu Tong; Liwei Li; Xiaolong Wang; Xutao Deng; Eric Delwart; et al. (Archives of Virology, 2019)

Residential emissions predicted as a major source of fine particulate matter in winter over the Yangtze River Delta, China - Yujie Wu; Peng Wang; Shaocai Yu; Liqiang Wang; Pengfei Li; Zhen Li; Khalid Mehmood; Weiping Liu; Jian Wu; Eric Lichtfouse; Daniel Rosenfeld; John H. Seinfeld (Environmental Chemistry Letters, 2018)

Novel Formulation Strategy to Improve the Feasibility of Amifostine Administration - Kavitha Ranganathan; Eric Simon; Jeremy Lynn; Alicia Snider; Yu Zhang; Noah Nelson; Alexis Donneys; Jose Rodriguez; Lauren Buchman; Dawn Reyna; Elke Lipka; Steven R. Buchman (Pharmaceutical Research, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Genetic variants in microRNA genes and targets associated with cardiovascular disease risk factors in the African-American population - Chang Li; Megan L. Grove; Bing Yu; Barbara C. Jones; Alanna Morrison; Eric Boerwinkle; Xiaoming Liu (Human Genetics, 2018)

How disturbance, competition, and dispersal interact to prevent tree range boundaries from keeping pace with climate change - Yu Liang; Matthew J. Duveneck; Eric J. Gustafson; Josep M. Serra‐Diaz; Jonathan R. Thompson (Global Change Biology, 2018)
Climate change is expected to cause geographic shifts in tree species' ranges, but such shifts may not keep pace with climate changes because seed dispersal distances are often limited and competition‐induced changes in community composition can be relatively slow. Disturbances may speed changes in community composition, but the interactions among climate change, disturbance and competitive interactions to produce range shifts are poorly understood. We used a physiologically based mechanistic landscape model to study these interactions in the northeastern United States. We designed a series of disturbance scenarios to represent varied disturbance regimes in terms of both disturbance extent and intensity. We simulated forest succession by incorporating climate change under a high‐emissions future, disturbances, seed dispersal, and competition using the landscape model parameterized with forest inventory data. Tree species range boundary shifts in the next century were quantified as the change in the location of the 5th (the trailing edge) and 95th (the leading edge) percentiles of the spatial distribution of simulated species. Simulated tree species range boundary shifts in New England over the next century were far below (usually

A Combination of Three Repurposed Drugs Administered at Reperfusion as a Promising Therapy for Postischemic Brain Injury - I-Chen Yu; Ping-Chang Kuo; Jui-Hung Yen; Hallel C. Paraiso; Eric T. Curfman; Benecia C. Hong-Goka; Robert D. Sweazey; Fen-Lei Chang (Translational Stroke Research, 2017)

Detection of a new species of torque teno mini virus from the gingival epithelium of patients with periodontitis - Yu Zhang; Fei Li; Xi Chen; Tong-Ling Shan; Xu-Tao Deng; Eric Delwart; Xi-Ping Feng (Virus Genes, 2017)

Deletion of a target gene in Indica rice via CRISPR/Cas9 - Ying Wang; Lizhao Geng; Menglong Yuan; Juan Wei; Chen Jin; Min Li; Kun Yu; Ya Zhang; Huaibing Jin; Eric Wang; Zhijian Chai; Xiangdong Fu; et al. (Plant Cell Reports, 2017)

Discovery and characterization of two new stem rust resistance genes in Aegilops sharonensis - Guotai Yu; Nicolas Champouret; Burkhard Steuernagel; Pablo D. Olivera; Jamie Simmons; Cole Williams; Ryan Johnson; Matthew J. Moscou; Inmaculada Hernández-Pinzón; Phon Green; Hanan Sela; Eitan Millet; et al. (Theoretical and Applied Genetics, 2017)

Implication of advanced glycation end products (Ages) and their receptor (Rage) on myocardial contractile and mitochondrial functions - Remi Neviere; Yichi Yu; Lei Wang; Frederic Tessier; Eric Boulanger (Glycoconjugate Journal, 2016)

On Creating Global Gridded Terrestrial Water Budget Estimates from Satellite Remote Sensing - Yu Zhang; Ming Pan; Eric F. Wood (Surveys in Geophysics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Phosphorus amendment mitigates nitrogen addition-induced phosphorus limitation in two plant species in a desert steppe, China - Juying Huang; Hailong Yu; Henry Lin; Yu Zhang; Eric B. Searle; Zhiyou Yuan (Plant and Soil, 2016)

Cytochrome P450 monooxygenase analysis in free-living and symbiotic microalgae Coccomyxa sp. C-169 and Chlorella sp. NC64A - Ntsane Trevor Mthakathi; Ipeleng Kopano Rosinah Kgosiemang; Wanping Chen; Molikeng Eric Mohlatsane; Thebeyapelo Jacob Mojahi; Jae-Hyuk Yu; Samson Sitheni Mashele; Khajamohiddin Syed (Algae, 2015)

Computational Fluid Dynamics Study of Bifurcation Aneurysms Treated with Pipeline Embolization Device: Side Branch Diameter Study - Abraham Yik-Sau Tang; Wai-Choi Chung; Eric Tian-Yang Liu; Jie-Qiong Qu; Anderson Chun-On Tsang; Gilberto Ka-Kit Leung; Kar-Ming Leung; Alfred Cheuk-Hang Yu; Kwok-Wing Chow (Journal of Medical and Biological Engineering, 2015)

PvNAC1 and PvNAC2 Are Associated with Leaf Senescence and Nitrogen Use Efficiency in Switchgrass - Jiading Yang; Eric Worley; Ivone Torres-Jerez; Randall Miller; Mingyi Wang; Chunxiang Fu; Zeng-Yu Wang; Yuhong Tang; Michael Udvardi (BioEnergy Research, 2015)

Enhanced diversity and aflatoxigenicity in interspecific hybrids of Aspergillus flavus and Aspergillus parasiticus - Rodrigo A. Olarte; Carolyn J. Worthington; Bruce W. Horn; Geromy G. Moore; Rakhi Singh; James T. Monacell; Joe W. Dorner; Eric A. Stone; De‐Yu Xie; Ignazio Carbone (Molecular Ecology, 2015)
Aspergillus flavus and A. parasiticus are the two most important aflatoxin‐producing fungi responsible for the contamination of agricultural commodities worldwide. Both species are heterothallic and undergo sexual reproduction in laboratory crosses. Here we examine the possibility of interspecific matings between A. flavus and A. parasiticus . These species can be distinguished morphologically and genetically, as well as by their mycotoxin profiles. Aspergillus flavus produces both B aflatoxins and cyclopiazonic acid ( CPA ), B aflatoxins or CPA alone, or neither mycotoxin; Aspergillus parasiticus produces B and G aflatoxins or the aflatoxin precursor O ‐methylsterigmatocystin, but not CPA . Only four of forty‐five attempted interspecific crosses between opposite mating types of A. flavus and A. parasiticus were fertile and produced viable ascospores. Single ascospore strains from each cross were shown to be recombinant hybrids using multilocus genotyping and array comparative genome hybridization. Conidia of parents and their hybrid progeny were haploid and predominantly monokaryons and dikaryons based on flow cytometry. Multilocus phylogenetic inference showed that experimental hybrid progeny were grouped with naturally occurring A. flavus L strain and A. parasiticus . Higher total aflatoxin concentrations in some F1 progeny strains compared to midpoint parent aflatoxin levels indicate synergism in aflatoxin production; moreover, three progeny strains synthesized G aflatoxins that were not produced by the parents, and there was evidence of allopolyploidization in one strain. These results suggest that hybridization is an important diversifying force resulting in the genesis of novel toxin profiles in these agriculturally important fungi.

Differential Field Responses of the Little Fire Ant, Wasmannia auropunctata (Roger), to Alarm Pheromone Enantiomers - Yang Yu; Eric B. Jang; Matthew S. Siderhurst (Journal of Chemical Ecology, 2014)

The Effect of Glutathione as Chain Transfer Agent in PNIPAAm-Based Thermo-responsive Hydrogels for Controlled Release of Proteins - Pawel W. Drapala; Bin Jiang; Yu-Chieh Chiu; William F. Mieler; Eric M. Brey; Jennifer J. Kang-Mieler; Victor H. Pérez-Luna (Pharmaceutical Research, 2014)

Epistasis in iron metabolism: complex interactions between Cp, Mon1a, and Slc40a1 loci and tissue iron in mice - Constance Delaby; Vincent Oustric; Caroline Schmitt; Francoise Muzeau; Anne-Marie Robreau; Philippe Letteron; Eric Couchi; Angel Yu; Saïd Lyoumi; Jean-Charles Deybach; Herve Puy; Zoubida Karim; et al. (Mammalian Genome, 2013)

Stachybotrys from soil in China, identified by morphology and molecular phylogeny - Chun-Yu Jie; Kun Geng; Yu-Lan Jiang; Jun-Jie Xu; Kevin D. Hyde; Eric H. C. McKenzie; Tian-Yu Zhang; Ali H. Bahkali; De-Wei Li; Yong Wang (Mycological Progress, 2013)

A novel Trichoderma species isolated from soil in Guizhou, T. guizhouense - Qi-Rui Li; Ping Tan; Yu-Lan Jiang; Kevin D. Hyde; Eric H. C. Mckenzie; Ali H. Bahkali; Ji-Chuan Kang; Yong Wang (Mycological Progress, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Postnatal exposure to voluntary exercise but not the antioxidant catechin protects the vasculature after a switch to an atherogenic environment in middle-age mice - Francois Leblond; Albert Nguyen; Virginie Bolduc; Jean Lambert; Carol Yu; Natacha Duquette; Eric Thorin (Pflügers Archiv - European Journal of Physiology, 2013)

Mechanisms of toxicity of triphenyltin chloride (TPTC) determined by a live cell reporter array - Guanyong Su; Xiaowei Zhang; Jason C. Raine; Liqun Xing; Eric Higley; Markus Hecker; John P. Giesy; Hongxia Yu (Environmental Science and Pollution Research, 2013)

Global climate change will severely decrease potential distribution of the East Asian coldwater fish Rhynchocypris oxycephalus (Actinopterygii, Cyprinidae) - Dan Yu; Ming Chen; Zhuocheng Zhou; Rochard Eric; Qiongying Tang; Huanzhang Liu (Hydrobiologia, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

A Study of the Intrinsic Autofluorescence of Poly (ethylene glycol)-co-( L -Lactic acid) Diacrylate - Yu-Chieh Chiu; Eric M. Brey; Víctor H. Pérez-Luna (Journal of Fluorescence, 2012)

Lack of ceruloplasmin expression alters aspects of copper transport to the fetus and newborn, as determined in mice - Yu-Ling Chu; Eric N. Sauble; Anthony Cabrera; Aleeza Roth; M. Leigh Ackland; Julian F. B. Mercer; Maria C. Linder (BioMetals, 2012)

Short-term effects of unilateral lesion of the primary motor cortex (M1) on ipsilesional hand dexterity in adult macaque monkeys - Shahid Bashir; Mélanie Kaeser; Alexander Wyss; Adjia Hamadjida; Yu Liu; Jocelyne Bloch; Jean-François Brunet; Abderraouf Belhaj-Saif; Eric M. Rouiller (Brain Structure and Function, 2012)

Harmonization of Regulatory Approaches for Evaluating Therapeutic Equivalence and Interchangeability of Multisource Drug Products: Workshop Summary Report - Mei-Ling Chen; Vinod P. Shah; Daan J. Crommelin; Leon Shargel; Dennis Bashaw; Masood Bhatti; Henning Blume; Jennifer Dressman; Murray Ducharme; Paul Fackler; Terry Hyslop; Lorelei Lutter; et al. (The AAPS Journal, 2011)

Mechanism of the Specific Neuronal Toxicity of a Type I Ribosome-Inactivating Protein, Trichosanthin - Ou Sha; David Tai-Wai Yew; Eric Yu-Pang Cho; Tzi-Bun Ng; Lin Yuan; Wing-Hang Kwong (Neurotoxicity Research, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Selective reduction of alcohol drinking in Sardinian alcohol-preferring rats by a sigma-1 receptor antagonist - Valentina Sabino; Pietro Cottone; Yu Zhao; Luca Steardo; George F. Koob; Eric P. Zorrilla (Psychopharmacology, 2009)

Copper binding components of blood plasma and organs, and their responses to influx of large doses of 65Cu, in the mouse - Anthony Cabrera; Erin Alonzo; Eric Sauble; Yu Ling Chu; Dionne Nguyen; Maria C. Linder; Dee S. Sato; Andrew Z. Mason (BioMetals, 2008)

New aspects of obscurin in human striated muscles - Lena Carlsson; Ji-Guo Yu; Lars-Eric Thornell (Histochemistry and Cell Biology, 2008)

Agrobacterium-mediated transformation of maize (Zea mays) with Cre-lox site specific recombination cassettes in BIBAC vectors - Juan M. Vega; Weichang Yu; Fangpu Han; Akio Kato; Eric M. Peters; Zhanyuan J. Zhang; James A. Birchler (Plant Molecular Biology, 2008)

Recent Origin of Dioecious and Gynodioecious Y Chromosomes in Papaya - Qingyi Yu; Rafael Navajas-Pérez; Eric Tong; Jon Robertson; Paul H. Moore; Andrew H. Paterson; Ray Ming (Tropical Plant Biology, 2008)

Toward closing rice telomere gaps: mapping and sequence characterization of rice subtelomere regions - Tae-Jin Yang; Yeisoo Yu; Song-Bin Chang; Hans de Jong; Chang-Sik Oh; Sang-Nag Ahn; Eric Fang; Rod A. Wing (Theoretical and Applied Genetics, 2005)

Modeling the dissemination of mammography in the United States - Kathleen A. Cronin; Binbing Yu; Martin Krapcho; Diana L. Miglioretti; Michael P. Fay; Grant Izmirlian; Rachel Ballard-Barbash; Berta M. Geller; Eric J. Feuer (Cancer Causes & Control, 2005)

Evidence for myofibril remodeling as opposed to myofibril damage in human muscles with DOMS: an ultrastructural and immunoelectron microscopic study - Ji-Guo Yu; Lena Carlsson; Lars-Eric Thornell (Histochemistry and Cell Biology, 2004)

The mode of myofibril remodelling in human skeletal muscle affected by DOMS induced by eccentric contractions - Ji-Guo Yu; Dieter O. Fürst; Lars-Eric Thornell (Histochemistry and Cell Biology, 2003)

A STEPWISE METHOD FOR THE ISOLATION OF ENDOTHELIAL CELLS AND SMOOTH MUSCLE CELLS FROM INDIVIDUAL CANINE CORONARY ARTERIES - MICHAEL K. DAME; XINWEN YU; ROSARIO GARRIDO; WALTER BOBROWSKI; J. ERIC MCDUFFIE; HEDWIG S. MURPHY; MUDHER ALBASSAM; JAMES VARANI (In Vitro Cellular & Developmental Biology - Animal, 2003)

Desmin and actin alterations in human muscles affected by delayed onset muscle soreness: a high resolution immunocytochemical study - Ji-Guo Yu; Lars-Eric Thornell (Histochemistry and Cell Biology, 2002)

Eccentric contractions leading to DOMS do not cause loss of desmin nor fibre necrosis in human muscle - Ji-Guo Yu; Christer Malm; Lars-Eric Thornell (Histochemistry and Cell Biology, 2002)

Human PRRX1 and PRRX2 genes: cloning, expression, genomic localization, and exclusion as disease genes for Nager syndrome - Russell A. Norris; Karen K. Scott; Clara S. Moore; Gail Stetten; Cuyler R. Brown; Ethylin Wang Jabs; Eric A. Wulfsberg; Jack Yu; Michael J. Kern (Mammalian Genome, 2000)

The photoreceptor cell-specific nuclear receptor gene ( PNR ) accounts for retinitis pigmentosa in the Crypto-Jews from Portugal (Marranos), survivors from the Spanish Inquisition - Sylvie Gerber; Jean-Michel Rozet; Shin-Ichiro Takezawa; Luisa Coutinho dos Santos; Lucilia Lopes; Olivier Gribouval; Clotilde Penet; Isabelle Perrault; Dominique Ducroq; Eric Souied; Marc Jeanpierre; Serge Romana; et al. (Human Genetics, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)